Respuesta :

Answer:

x=3, y=0

Step-by-step explanation:

Answer:

(3, 0 )

Step-by-step explanation:

Given the 2 equations

2x + 2y = 6 → (1)

4x - 6y = 12 → (2)

Multiplying (1) by - 2 and adding to (2) will eliminate the x- term

- 4x - 4y = - 12 → (3)

Add (2) and (3) term by term to eliminate x

0 - 10y = 0

- 10y = 0 ⇒ y = 0

Substitute y = 0 into either of the 2 equations and solve for y

Substituting into (1)

2x + 2(0) = 6

2x = 6 ( divide both sides by 2 )

x = 3

solution is (3, 0 )